Asymmetry Effect on Hydrodynamic Characteristics of Double Chamber Oscillating Water Column Device - R, Wilbert; V, Sundar; S.A, Sannasiraj (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Awakening of renewable energy in the latter half of the twentieth century has identified wave energy as a potential source of clean energy due to its high intensity of energy flux compared with other renewable sources of energy. Subsequent research found out that Oscillating Water Column (OWC) concept is an easier and simple technology to harness energy from the Ocean waves. This had lead to a rapid progress in research pertaining to tuning of the system for optimum efficiency. The Double Chamber Oscillating Water Column (DCOWC) concept is a modified form of OWC. The present study is an extension of previous studies for understanding its hydrodynamics with respect to its two geometric parameters; bottom opening and front duct width. The experimental works carried out on a scaled down model for identifying the effective combination between them is explained. The hydrodynamic principles governing the maximum harness of wave energy is detailed here. The discussions related to wave energy absorption, wave energy conversion, phase angle difference between pressure excitation and air pressure and wave amplification which govern the efficiency of the DCOWC are included for a better understanding on the effect between geometry and wave characteristics. It is expected that the findings of this study enhance knowledge on the hydrodynamic aspects of the concept of a DCOWC.